FRAMING DEVICE IN GAMSON AND MODIGLIANI MODEL ABOUT THE NEWS OF KOMISI PEMBERANTASAN KORUPSI - Febriana, Ratih Putri; Sukarelawati, Sukarelawati; Fitriah, Maria (Universitas Djuanda Bogor, 2020)
Firli Bahuriâ€™s election as chairman of Komisi Pemberantasan Korupsi, and efforts to revise the laws of anti-corruption Commission triggered the noise, the media have a responsibility to tell it. Each media has constructed the news of KPK withÂ differently. The problem in this study is